Integrative phylogenomics reveals a Permian origin of Adephaga beetles. (26th July 2021) - Baca, Stephen M.; Gustafson, Grey T.; Alexander, Alana M.; Gough, Harlan M.; Toussaint, Emmanuel F. A.
Abstract: Beetles are arguably the most diverse group of animals on Earth with over 400 000 described species. Yet the timing of main diversification events among these insects remains debated. The use of phylogenomic data generated using next‐generation sequencing recently resolved most recalcitrant phylogenetic relationships across Coleoptera. However, limited taxon sampling for some major clades still prevents the use of important fossil calibrations that could provide more accurate estimates of the timing of lineage diversification events among beetles. Here, we present a new fossil‐based dated framework with a focus on the suborder Adephaga. We rely on an integrative phylogenomic approach using a combination of genomic, ultraconserved element and RNAseq transcriptomic datasets, further revealing the prevalent exonic nature of ultraconserved elements in Coleoptera. We infer a robust phylogenomic tree under various optimality criteria and analytical conditions. Our preferred phylogenetic reconstruction is consistent with those of previous phylogenomic studies in recovering the paraphyly of 'Hydradephaga', Gyrinidae as sister to all other Adephaga, the monophyly of Geadephaga and Haliplidae as sister to a monophyletic Dytiscoidea. We further recover strong support for paraphyly of Aspidytidae and the placement of Hygrobiidae as part of a clade comprising Aspidytes, Ribera, Beutel, Balke & Vogler, Sinaspidytes Balke, Beutel & Ribera and Amphizoidae. Using 23 carefully chosen fossil calibrations across Coleoptera, we infer the origin of modern beetles ca. 317 Ma in the mid‐Carboniferous, the divergence between Archostemata and Adephaga ca. 296 Ma in the early Permian, and the crown of Adephaga in the end‐Permian ca. 255 Ma. Importantly, our analyses provide more precise estimates of divergence times for internal splits within Adephaga, including ground beetles, tiger beetles and aquatic adephagan lineages. These results represent a major step forward in our understanding of beetle diversification and will serve as a fundamental framework to unravel the evolutionary history of many clades within Adephaga. Abstract : An ultraconserved element dataset is assembled from genomic, RNAseq and ultraconserved element‐enriched reads to produce robust taxon sampling for a phylogenomic analysis of Adephaga. Divergence times are estimated using 23 coleopteran fossils, recovering an end‐Permian crown age for Adephaga (255 Ma) with higher‐level relationships within Adephaga stable. The primarily exonic nature of ultraconserved elements within Coleoptera is further revealed and the compatibility of ultraconserved element probe sets with diverse read types is demonstrated.